Математическая модель однофазного конденсаторного асинхронного электродвигателя - Анищенко, Николай Васильевич; Астапов, А. А. (НТУ "ХПИ", 2009)
Разработана математическая модель и структурная схема однофазного асинхронного конденсаторного двигателя методом продольного и поперечного полей (метод двух реакций). Адекватность модели проверена путем компьютерного моделирования с использованием пакета MATLAB.

A mathematical model and a diagram of the monophase condenser asynchronous electric motor are developed using a method of longitudinal and transversal fields components (the method of two reactions). The model adequacy is tested by a computer modeling on the base of the MATLAB package.
Mathematical model of the monophase condenser asynchronous electric motor
Keywords: ОКАД; обмотка статора; система координат; mathematical model; monophase asinchronous motor; condenser